On Dependence of Mechanical Properties of Brittle Material on Partial Concentrations of Different Sized Pores in its Structure in a Wide Range of Porosity; AIP Conference Proceedings; Vol. 1683 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures - Konovalenko I. S. Igor Sergeevich (2015, 2015)
Title screen